1995
DOI: 10.1111/j.1476-5381.1995.tb15946.x
|View full text |Cite
|
Sign up to set email alerts
|

An endogenous protectant effect of cardiac cyclic GMP against reperfusion‐induced ventricular fibrillation in the rat heart

Abstract: 1 After a period of myocardial ischaemia, reperfusion of the myocardium can elicit cardiac arrhythmias. Susceptibility to these arrhythmias declines with time, such that a preceding period of more than approximately 40 min ischaemia is associated with few reperfusion-induced arrhythmias. We have tested the hypothesis that this decline in susceptibility occurs, in part, because of protection by endogenous guanosine 3':5'-cyclic monophosphate (cyclic GMP). 2 Rat isolated hearts were subjected to 60 min left regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The NO-induced production of cGMP in the myocardium plays an important role in the antiarrhythmic effect of NO (34). The increase in myocardial cGMP inhibits Ca 2ϩ influx through L-type Ca channels and reduces Ca 2ϩ overload during I/R (35).…”
Section: Discussionmentioning
confidence: 99%
“…The NO-induced production of cGMP in the myocardium plays an important role in the antiarrhythmic effect of NO (34). The increase in myocardial cGMP inhibits Ca 2ϩ influx through L-type Ca channels and reduces Ca 2ϩ overload during I/R (35).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in intracellular cGMP concentrations. These results demonstrated that methylene blue, a soluble guanylate cyclaseinhibitor, raised the incidence of reperfusion-induced ventricular arrhythmias in isolated rat hearts and that M&B22948 abolished this effect of methylene blue through an increase in ventricular cGMP content [39]. In addition, cGMP-mediated inhibition of L-type Ca 2ϩ channel activity in cardiac myocytes has shown that cGMP could play a physiological role in cardiac functions [40].…”
Section: Discussionmentioning
confidence: 99%
“…Rapid pacing-induced slight ischaemia and mechanical stress result in a release of several ischaemic metabolites from the myocytes and/or coronary endothelium, which in turn activate the capsaicin-sensitive sensory nerve endings. The concomitant neural release of NO and/or CGRP leads to an activation of K ATP and an increase in cGMP concentration, which may significantly contribute to the cardioprotective effect of preconditioning (Szilvassy et al 1993(Szilvassy et al , 1994aPabla et al 1995;Gross and Auchampach 1992). We conclude that the presence of an intact local sensory innervation is a prerequisite to elicit pacing-induced preconditioning; that a significant portion of basal cardiac NO content may be derived form capsaicin-sensitive neural sources; and that NO and CGRP released from these nerve fibres may be involved in the mechanism of pacing-induced preconditioning in the rat heart.…”
Section: Mechanism Of Pacing-induced Preconditioning: a Hypothesismentioning
confidence: 99%